PROPOSITIONING THE POWER OF RUSSIA THROUGH METAPHORICAL CONCEPTS AND CONSTRUCTION: A STUDY OF AL-JAZEERA POSTED CARTOONS - Maria Saleem; Fariah Farooq Khan; Ishrat Ranjhani; Muhammad Rashid (International Journal of Contemporary Issues in Social Sciences, 2024)
The present study is a timely and relevant exploration of the Al-Jazeera conceptual and constructive meanings of the power of Russia, as depicted in the cartoons posted in different articles on online news websites. The descriptive study has adopted Jose J. Riera's (2020) semiotic analysis model, which has three major aspects: Concept, Construct, and Proposition. We have meticulously selected five cartoons for analysis based on the invasion of Russia, atomic deployment, media, and African and European perspectives. The domains and the cartoons were selected using purposive sampling. The cartoons are selected and published during the year 2022. The study finds that the signs are presented based on the ground realities while the construction of the signs is based on the power stretches in which Russia is presenting as the dominant. The recipient of the sender’s message can define that the power of the Russian Federation is dominant in all domains. At the same time, the passivity of Ukraine and the Western countries is evident as they are helpless in the War. The study also finds that the wrath of the Russian invasion is presented with full power, while the resistance of Ukraine is not presented powerfully. Atomic reducing policy is presented as the deploying and usage of the atom bombs to special targets in Ukraine, which is the discursive practice. Western perspectives are perceived as helpless, while the African perspective is neutral. On the other hand, the media is depicted as loaded with national discourse and narrative change according to the changing ground situations.